Managing Orthopaedic Injuries in Covid-19 Pandemic : A Consise Review (Global Journal of Medical Research, 2021)
Conservative, non-operative therapeutic approach may provide an alternative in nonobligatory fractures in the current COVID-19 pandemic and perhaps later on as well. It may serve as a route for us to manage orthopaedic injuries till we tide over the peak of the pandemic and resume elective surgeries. Perhaps, the Coronavirus crises has given us this unique opportunity to rethink and revisit traditional methods of treating fractures and the tolerance to operate every limb fracture must be risen. We must realize that all the fractures do not always need operative management and the conservative management still has a certain place in our armamentarium of fracture management, in an evolving world.
Keywords: orthopaedic injuries; trauma; COVID-19; non-operative management; fracture; dislocation